The Determinants of Diarrhea Disease Incidence in Densely Populated Area of West Nusa Tenggara, Indonesia - Siwi Pramatama Mars Wijayanti; Muhamad Sidik; Achmad Iqbal (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: Diarrhoea due to water borne diseases is still prevalent in Indonesia and this environmental health problem could triggered outbreaks in multiple regions. Objectives: The aim of this study was to determine the correlation of environmental factors, behavior and quality of water to the incidence of diarrhea in densely populated settlements in Rasanae Barat District, Bima City. Method: This study used cross sectional design and the data was obtained by survey and interview using questionnaire. The population in the study was all residents who lived permanently in the Rasanae Barat District of Bima City. The sample size is 192 which determined by formula for testing the proportion of a single population. Variables of this study were environmental factors (distance of clean water facilities with latrines (septic tanks) and waste bins facilities), behavioral factors (knowledge, and attitude) and water quality (total coliform). Data analysis was carried out includes univariate, bivariate by chi-square statistical test. and multivariate analysis by multiple logistic regression. Results and Discussion: Based on the results of the study, it showed that the variables associated with the incidence of diarrhea were water quality (total coliform) (p=0,000), and knowledge (p= 0.003). Conclusion: Since the variables that have significant association to diarrhea were water quality and knowledge, so it is important for community to build septic tank with requirement standard to overcome the land limitation. Health institution also need to conduct periodic water quality checks and also increase community knowledge about water quality and diarrhea prevention. This study could provide valuable input for diarrhea prevention and control program.